Last in, first out? Estimating the effect of seniority rules in Sweden - David von Below; Peter Skogman Thoursie (Institute for Labour Market Policy Evaluation (IFAU), 2008)
In this paper we investigate whether a relaxation in seniority rules (the last-in-first-out-principle) had any effect on firms' employment behaviour. Seniority rules exist in several countries and, like Sweden, most European countries have a more lenient employment protection for firms below a certain size. Despite the fact that small firms represent a large share of all firms and stand for a substantial share of total employment, there is limited knowledge of how such exemption rules affect firms' employment behaviour - the consequences of seniority rules on firms' employment behaviour have not been examined at all. Using data including the population of firms matched with the population of workers for the period 1999-2002, we do not find any general effects on worker flows or on hires and separations. The only exception is a tendency of an increase in the share of separations for older workers and workers with longer seniority. The result points to the importance of considering in detail how legislation is formulated and how it works in practice.
Keywords: E24; J63; J65; 330; Employment protection; employment change; hires; separations; Regression discontinuity; Kündigungsschutz; Kündigung; Arbeitsmobilität; Ältere Arbeitskräfte; Klein- und Mittelunternehmen; Schweden